Executing optimized throwing motion on robot arm with free joint. (16th December 2016) - Kim, Chyon Hae; Sugano, Shigeki
Graphical Abstract: Abstract : We address the throwing motion optimization for robot. In order to pursue the best throwing motion, we may need heuristics/intuition free methods. We propose a throwing method that is composed of rapid semi-optimal motion-planning and output zeroing method. So as to execute the optimized trajectories in real rigid body systems, we need some compensations for the noises around the optimized trajectories. We introduce a compensation method for the optimized throwing motions of a robot arm with a free joint. To validate the effectiveness of the proposed method, we conducted a throwing experiment using a two-link arm. As a result of the experiment, the robot arm threw a ball with 63.7 km/h, which was the best record through the past experiments of this arm.